2022
DOI: 10.3390/ani12243476
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants and Fatty Acid Profile in a Typical Cheese from Extensive Farms: First Assessment of Human Exposure by Dietary Intake

Abstract: Dairy products represent an important source of beneficial substances for humans. At the same time, they can expose the consumers to environmental contaminants ingested by animals through their diet, influencing their health negatively. This experiment aims to evaluate the risk and benefits related to the consumption of typical stretched cheeses, considering their fatty acid (FA) profile and persistent organic pollutants (POPs) content. Six representative farms, two of them organic, raising Cinisara cattle wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
(169 reference statements)
0
4
0
1
Order By: Relevance
“…Asimismo, varios COP muestran asociaciones positivas con marcadores de lesión hepática y la incidencia de enfermedad hepática, lo que sugiere que las toxinas ambientales son factores de riesgo importantes para la enfermedad hepática crónica, según indican los estudios de Hakkarainen et al (2023). En algunas muestras sobre estudios de la presencia de COP en la cadena alimenticia se encontraron niveles de PCB considerados peligrosos para la salud humana (Giosuè et al, 2022). Una gran cantidad de estudios han corroborado una asociación entre la disbiosis microbiana intestinal inducida por COP y la prevalencia de trastornos.…”
Section: Los Contaminantes Orgánicos Persistentes Y Su Impacto En La ...unclassified
“…Asimismo, varios COP muestran asociaciones positivas con marcadores de lesión hepática y la incidencia de enfermedad hepática, lo que sugiere que las toxinas ambientales son factores de riesgo importantes para la enfermedad hepática crónica, según indican los estudios de Hakkarainen et al (2023). En algunas muestras sobre estudios de la presencia de COP en la cadena alimenticia se encontraron niveles de PCB considerados peligrosos para la salud humana (Giosuè et al, 2022). Una gran cantidad de estudios han corroborado una asociación entre la disbiosis microbiana intestinal inducida por COP y la prevalencia de trastornos.…”
Section: Los Contaminantes Orgánicos Persistentes Y Su Impacto En La ...unclassified
“…Moreover, certain probiotic strains in cheese-making have been shown to enhance the bioactive peptide content. A study on cheddar cheese showed that using Lactobacillus casei 300 resulted in the formation of peptides with antihypertensive activity [11]. Moreover, the utilization of specific enzymes, such as proteases, in the cheese production process has demonstrated the ability to augment the presence of bioactive peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of plant-based diets, such as flaxseed, in dairy animals has been demonstrated to enhance the nutritional profile of cheese [10,11]. Flaxseed is recognized as a substantial reservoir of α-linolenic acid, classified as an omega-3 fatty acid, and widely acknowledged for its advantageous impact on cardiovascular well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Von Grebmer et al [ 12 ] support this finding, emphasizing the need for addressing food systems transformation and local governance to combat hunger. However, akin to other animal products [ [13] , [14] , [15] , [16] ], snails can accumulate various contaminants, including heavy metals, polycyclic aromatic hydrocarbons (PAHs), polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs), originating from waste byproducts (gases, particles, sludge, liquid effluent) released into the environment, primarily from industrial activities. Many of these compounds are highly toxic and persist in the environment, posing significant risks to both human and ecosystem health [ 13 , 16 ] and having the potential to result in carcinogenic outcomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%